Perbaikan Sampan Komposit Sandwich Oleh Nelayan Desa Kuranji - Setyawan, Paryanto Dwi; Agus Dwi Catur; Sugiman, Sugiman; Salman, Salman (JURNAL KARYA PENGABDIAN, 2025)
Fishermen from Kuranji Village catch fish every day in the Lombok Strait. The sampan (small boat) made from sandwich composite material that has been used for 6 years has been damaged in several parts and has decreased in function. The problems faced by fishermen are solved by empowering them. The service team trains fisherman to solve their problems so they have skills in repairing boats with sandwich composite hulls, so that they do not have to incur additional repair costs. The preparations made are preparing activity materials, preparing tools and materials. The activity implementation stage is the most decisive stage which consists of repairing sandwich composite boats by fishermen. The evaluation stage is carried out for each activity, the seriousness and skills of partners in repairing the boat are observed. Partners are able to repair damage to boats made from sandwich composites independently, this indicates that partners have good practical knowledge after being trained by the service team.